Contemporary demographics, diagnostics and outcomes in non-bacterial thrombotic endocarditis. Issue 20 (9th May 2022) - Quintero-Martinez, Juan A; Hindy, Joya-Rita; El Zein, Said; Michelena, Hector I; Nkomo, Vuyisile T; DeSimone, Daniel C; Baddour, Larry M
Abstract : Objective: Non-bacterial thrombotic endocarditis (NBTE) is a syndrome characterised by cardiac valve vegetations and/or thickening due to non-infective mechanisms. Nowadays, a premortem diagnosis of NBTE is possible based on echocardiographic findings. Therefore, to better characterise this disease, we performed a contemporary review of the epidemiology, demographics, diagnosis and clinical outcomes of these patients. Methods: Adults with a diagnosis of NBTE seen within the Mayo Clinic Enterprise from December 2014 to December 2021 were included. NBTE diagnosis was identified by clinicians representing at least two specialties including cardiology, infectious diseases, rheumatology and oncology. Patients with positive blood cultures, infective endocarditis, culture-negative endocarditis and denial of research authorisation were excluded. All patients had a 1-year follow-up. Results: Forty-eight cases were identified; mean age was 60.0±13.8 years, 75% were female. The most prevalent comorbidities were malignancy (52.1%) and connective tissue disease (37.5%). Valvular abnormalities included 41 (85.4%) patients with vegetations, 43 (89.6%) patients with thickening and 26 (54.2%) with moderate to severe regurgitation. Thirty-eight (79.2%) patients had an embolic event (stroke in 26 (54.2%) patients) within 1 month of NBTE diagnosis and 16 (33.3%) patients died within 1 year of NBTE diagnosis. Metastatic tumours and lung cancer were associated with 1-year all-cause mortality (p=0.0017 and p=0.0004, respectively). Conclusions: NBTE was more prevalent in females and embolic complications were the most frequent clinical finding. Overall, patients with NBTE had a poor prognosis, particularly in those with lung cancer or metastatic tumours. Further studies in patients with NBTE are needed given its morbidity and mortality.